The Thanksgiving hymns - Mansoor, Menahem. (Studies on the Texts of the Desert of Judah, 1961)
The Scroll of the Hodayot or Thanksgiving Hymns was found in a cave, generally known as Cave One, in the vicinity of Khirbet Qumran on the northwestern shore of the Dead Sea in the spring of 1947, together with other scrolls and fragments of manuscripts. The Thanksgiving Scroll was found in two parts. One contained three separate folded sheets. The second part was a crumpled mass of some seventy fragments by the time it reached the hands of scholars at the Hebrew University of Jerusalem. The text, on the whole, is poorly preserved. - pages [1] - [4].